FONTES DE ADUBAÇÃO NITROGENADA E SEUS REFLEXOS SOBRE O INCREMENTO DE AFILHAMENTO EM CULTIVARES DE TRIGO - VALENTINI, ANA P. F.; PARAGINSKI, ANTÔNIO; ZAMBONATO, FELIPE; GAVIRAGHI, FERNANDO; MARTINS, JOÃO A. K.; SILVA, JOSÉ A. G. D.; WAGNER, JULIANO F.; UHDE, LEONIR; CARBONERA, ROBERTO; CIOTTI, RODRIGO; et al. (Salão do Conhecimento, 2013)
Resumo